Transformation of the historical territory under the impact of the urban load. Jelgava example - Ziemeļniece, Aija (Journal of Architecture and Urbanism, 2016)
One of the most important issues in Latvia after gaining independence, as in all post-socialism countries, is the assessment and further development of the economic potential and the related urban space structure. The socio-economic preconditions of planning of the urban construction environment and the architectural spatial transformation are associated with the building reconstruction and regeneration. Today, an integral part of the transformation of inhabited areas is also building renovation and injection of landscape elements in the mechanical structures of the development plans of the Soviet times. These measures ensure a harmonious balanced living space and corresponding living conditions for residents (Treija et al. 2010). The transformation process of the image of the architecturally spatial environment of inhabited areas is dynamic in its nature. This process is affected by socio-economic and engineering opportunities, as well as the peculiarities of the artistically aesthetic perception of the corresponding period. The image of the urban space has a very strong spiritual aura, which arises a series of thoughts, associations, views and emotions (Ziemeļniece 2010). The main task of the compositional image of the urban environment is to generate positive feelings in the population or in each traveler who visits the particular settlement. The Latvian historical localities – cities, manor ensembles, farmstead groups – over the centuries have been created as grid structures, where the social and economic activities overlap, according to the settlement function, scale and reachability (Briņķis, Buka 2006).